2020
DOI: 10.1007/s11426-019-9680-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into the novel glucose-sensitive behavior of P(NIPAM-co-2-AAPBA)

Abstract: Aglucose-sensitive polymer, poly(N-isopropylacrylamide-co-2acrylamidophenylboronic acid) (P(NIPAM-co-2-AAPBA)), was synthesized by RAFT copolymerization. Addition of glucose results in reduced solubility and hence increased turbidity, rather than the normal increase in solubility (decreased turbidity) observed for other PBA-based glucose-sensitive polymers. The novel glucose-sensitive behavior is explained by a new mechanism, in which glucose acts as an additive and depresses the lower critical solution temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…2 d. It was observed that with an increase in the AAPBA ratio, the zeta potential of nano-gels became increasingly negative, which may be due to the higher hydrophobic AAPBA content, protecting them from any damage in the aqueous solution and providing relative stability. This is consistent with relevant studies [ 32 ], suggesting that p(AAPBA-b-HPA) nanoparticles are stable in aqueous solutions.…”
Section: Resultssupporting
confidence: 93%
“…2 d. It was observed that with an increase in the AAPBA ratio, the zeta potential of nano-gels became increasingly negative, which may be due to the higher hydrophobic AAPBA content, protecting them from any damage in the aqueous solution and providing relative stability. This is consistent with relevant studies [ 32 ], suggesting that p(AAPBA-b-HPA) nanoparticles are stable in aqueous solutions.…”
Section: Resultssupporting
confidence: 93%
“…Equilibrium composition in aqueous medium at 25 °C in sucrose is 6% β-furanose and 10% α-furanose, in D-galactose it is 8.4% α-furanose and 15.5% β-furanose. The only significant forms in sucrose are α and β pyranose forms whereas α and β furanose forms in water are only about 0.08% at 31 °C 30 , 44 , 45 , 46 , 47 ]. Our study also shows the effect of these changes in structure on the binding process.…”
Section: Resultsmentioning
confidence: 99%
“…Boronic acids are continuing to gain interest in scaffold designing of sensors for carbohydrate cognition because of their high sugar intrinsic affinity and reversible rapid equilibrium. Even in simple cells, carbohydrates are found to be endogenous and vital in many of the biochemical processes [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Also, they are often linked to proteins that affect activity and cell surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations